The history of the Moravian Brass Band Union of South Africa (BBSA) as told through the personal histories of members, and its contemporary role in the Moravian Church in South Africa (MCSA) - Joorst, Rudolph Zacharias (Stellenbosch : Stellenbosch University, 2025)
Thesis (MMus)--Stellenbosch University, 2025.